Synergistic Effect of Nitric Oxide Synthase and Cyclooxygenase Inhibitors on Carrageenan-induced Paw Edema in Rats - Sakaguchi, Yasue; Shirahase, Hiroaki; Kunishiro, Kazuyoshi; Ichikawa, Atsuko; Kanda, Mamoru; Uehara, Yoshio (Arzneimittelforschung, 2006)
The present study examined the effects of L-nitroarginine methylester (L-NAME, CAS 50903–99–6), a non-selective nitric oxide synthase (NOS) inhibitor, indometa-cin (IND, CAS 3305–29–1), a non-selective cyclooxygenase (COX) inhibitor, and a combination of these agents (L-NAME + IND) on carrageenan-induced paw edema for 4 h after the injection of carrageenan in rats. L-NAME at 10 and 30 mg/kg but not 3 mg/kg (i.p.) decreased paw volume slightly but significantly only at 1 h after the carrageenan injection. IND reduced paw volume slightly at 1 and 3 mg/kg, and markedly at 10 mg/kg (p.o.). A combination of L-NAME and IND at a subthreshold dose (3 mg/kg, i.p. and 1 mg/kg, p.o., respectively) caused a marked reduction of paw edema, which was also confirmed by histopathological examinations. A combination of N-(3-(aminomethyl)benzyl)acetamidine (1400W, CAS 180001–34–7), a selective inhibitor of inducible NOS, and IND at 3 mg/kg, i.p., and 1 mg/kg, p.o., respectively, did not show synergistic anti-inflammatory effects. In conclusion, the combination of non-selective NOS and COX inhibitors had synergistic anti-inflammatory effects on carrageenan-induced paw edema at an early stage, suggesting negative crosstalk between the endogenous NOS-NO and COX-PG pathways in the early stages of acute inflammation.
Keywords: Anti-inflammatory drugs, non-steroidal; Carrageenan; CAS 3305–29–1; CAS 50903–99–6; Indometacin; L-Nitroarginine methylester; Paw edema, rat